Mechanical Properties and UV Curing Behavior of Poly(N‐Isopropylacrylamide) in Phosphonium‐Based Ionic Liquids. Issue 7 (17th January 2013) - Ziółkowski, Bartosz; Ates, Zeliha; Gallagher, Simon; Byrne, Robert; Heise, Andreas; Fraser, Kevin J; Diamond, Dermot
Abstract N‐isopropylacrylamide (NIPAM) is photopolymerized in a range of phosphonium‐based ionic liquids (ILs). The curing behaviour of polymer‐IL solutions (linear pNIPAM) and ionogels (crosslinked pNIPAM) is studied using rheometry, DSC, and GPC. It is found that the IL influences the mechanical properties, the rate of polymerization, and the LCST of the resulting pNIPAM ionogels. Ionogels made in trihexyl‐tetradecyl phosphonium dicyanamide show an order of magnitude smaller ratio of loss/storage moduli compared to that of trihexyl‐tetradecyl phosphonium chloride, and a doubling of the UV polymerization rate. Temperature‐ramp rheology scans of the water‐swollen ionogels show that upon LCST transition the moduli of the polymer network exhibit anion dependent increases.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>